Alpha Anomers of iGb3 and Gb3 Stimulate Cytokine Production by Natural Killer T Cells - Yin, Ning (2009)
Natural killer T cells (NKT cells) respond to presentation of specific glycolipids with release of a variety of proinflammatory and immunomodulatory cytokines. The repertoire of glycolipid antigens for these cells includes α-glycosylceramides, α-glycosyldiacylglycerols, and the triglycosylceramide iGb3. Two features of iGb3 set it apart from these other antigens: (1) three sugars are required for stimulation and (2) the glycosidic bond between ceramide and the proximal sugar is beta in iGb3 whereas it is alpha in other antigens. We have synthesized the alpha versions of iGb3 and Gb3 and demonstrate that they are effective antigens for NKT cells and that they do not require lysosomal processing to the monoglycosylceramides for stimulation. These triglycosylceramides constitute a new class of antigen that stimulates NKT cells comparably to monoglycosylceramides.